2020
DOI: 10.3390/ijms21114140
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Non-Genomic Mechanisms of Action of Thyroid Hormones and Their Catabolite 3,5-Diiodo-L-Thyronine in Mammals

Abstract: Since the realization that the cellular homologs of a gene found in the retrovirus that contributes to erythroblastosis in birds (v-erbA), i.e. the proto-oncogene c-erbA encodes the nuclear receptors for thyroid hormones (THs), most of the interest for THs focalized on their ability to control gene transcription. It was found, indeed, that, by regulating gene expression in many tissues, these hormones could mediate critical events both in development and in adult organisms. Among their effects, much attention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 328 publications
(524 reference statements)
0
52
0
3
Order By: Relevance
“…Metabolic products of inadequate fatty acid oxidation set off and worsen liver inflammation, fibrosis, and necrosis [ 155 , 156 ]. Recently the 3,5-diiodo-L-thyronine (3,5-T2) molecule has attracted more attention because of its metabolic effects, which are similar to T3, but mainly because of its beneficial actions on mitochondrial function and oxidative stress, which suggest its future introduction as a potential clinical drug [ 157 ]. More data are needed regarding inflammation and oxidative stress in HIN, which may bring interesting possibilities of new therapeutic targets or biomarkers.…”
Section: Immunopathogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolic products of inadequate fatty acid oxidation set off and worsen liver inflammation, fibrosis, and necrosis [ 155 , 156 ]. Recently the 3,5-diiodo-L-thyronine (3,5-T2) molecule has attracted more attention because of its metabolic effects, which are similar to T3, but mainly because of its beneficial actions on mitochondrial function and oxidative stress, which suggest its future introduction as a potential clinical drug [ 157 ]. More data are needed regarding inflammation and oxidative stress in HIN, which may bring interesting possibilities of new therapeutic targets or biomarkers.…”
Section: Immunopathogenesismentioning
confidence: 99%
“…MGL-3196 also has a very high protein bound (above 99%) with very good hepatic tissue penetration, showing specificity for the liver. Testing of resmetirom on animal models showed that it has an important role in reducing hepatic triglycerides, lipid peroxidation, ALT, steatosis, inflammation, and fibrosis [ 157 , 205 ]. In a 36-week randomized study that was double-blinded and placebo-controlled and took place in 25 USA centers, only adults with biopsy confirmed NASH (stages 1–3 of fibrosis) were enrolled and the eligible ones were those who had a hepatic fat fraction above 10% at MRI-proton density fat fraction (MRI-PDFF).…”
Section: Thr-β Selective Thyromimetics and Nafldmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to modulate chromatin structure, thus regulating the accessibility of genes to RNA polymerase, a few interrelated mechanisms are required: (i) post-translational modification of histone proteins; (ii) modification of site-specific DNA methylation; (iii) changes in the activity of ATP-dependent chromatin remodeling complexes, such as the chromodomain helicase DNA-binding (Chd) family of enzymes; and (iv) synthesis and incorporation into chromatin of histone variants [ 21 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Now, the nuclear receptors for thyroid hormones (THRs) can bind to chromatin and, depending on the presence of T3 and/or other regulatory factors, can recruit chromatin remodeling complexes and/or histone-modifying activities, thus causing the chromatin structure and gene expression to change [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Notably, during their terminal differentiation, cortical neurons acquire a short average spacing of nucleosomes (about 165 bp), while glial cells have a longer nucleosomal length, similar to most other cell types [ 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Thyroid hormones regulate several genes involved in lipolysis, lipogenesis, thermogenesis, mitochondrial function and nutrient availability. 9,10 Due to their effects on the cardiovascular system and heart's rhythm, thyroid hormones, cannot be used as a pharmacological agents for the treatment of obesity. Many recent studies have highlighted that a metabolite of thyroid hormones, namely 3,5-diiodo-L-thyronine (T2) is endowed with interesting metabolic activities that may be of clinical interest as possible, future therapeutic option in the treatment overeating disorders.…”
Section: Introductionmentioning
confidence: 99%